Motion planning of piezoelectrically driven micro-robots via navigation functions - Kyriakopoulos, Kostas J.; Loizou, Savvas (My University, 2005)
In this paper we present a closed loop switching control methodology applicable to piezoelectrically driven micro-robots whose locomotion principle is based on the stick slip effect. The derived controller has theoretically guaranteed global convergence and collision avoidance properties. The effectiveness of the proposed methodology is verified through hardware experiments and computer simulations.
Keywords: Computer simulation; Navigation; Robots; Hardware